New approaches to pediatric treatment of post-traumatic elbow contractures - Gairat D. Bayimbetov (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Introduction Post-traumatic elbow contracture is a severe disabling condition of childhood that interferes with both physical and psychic aspects for the child. A high rate of poor results encourages surgeons seek for better surgical treatments. Current diagnostic modalities were practical to get the clinical picture of the contracture mechanogenesis and determine the treatment strategy. The goal of the study was to review long-term results of new surgical techniques developed for post-traumatic elbow contractures in children. Material and methods The inpatient records of 102 pediatric patients with post-traumatic elbow contractures operated on with the technique offered were reviewed. All patients underwent conventional radiological, ultrasound and MSCT examinations. Results Based on the pathobiomechanics of the injured elbow a mobilization technique was developed to ensure complete bone realignment, relieve pain and allow early exercises for the joint. Postoperative lavage of the joint cavity, intra-articular administration of corticosteroids and polyvalent enzymes in the early postoperative period facilitated improved long-term outcomes of elbow contractures. All patients reported good results. Discussion Tenotomies of the lateral ligaments can be added to arthrotomy and reconstruction of articular surfaces for temporary instability of the joint to restore movement in the elbow joint in severe cases. Post-traumatic elbow contractures are accompanied by impaired biomechanics. MSCT and 3D reconstruction of bone structures is the gold standard in the diagnosis of post-traumatic elbow contractures. Conclusion Bone impingements are to be addressed and an extended mobilization of the capsular ligamentous complex be provided for complete movement recovery through partial elbow instability to be temporarily ensured. Prolonged lavage of the elbow joint can be used to prevent adhesions and allow early elbow exercises and provide improved outcomes.